Retraction Notice for "Preconception Care through Religious Leaders in Bangladesh - A Novel Approach" (Delta Medical College Journal, 2019)
On 18th March 2019 the Editorial Board of Delta Medical College Journal agreed to retract the Editorial 'Preconception Care through Religious Leaders in Bangladesh – A Novel Approach’ published in Delta Medical College Journal, Vol.6(2) pages 59-61 (DOI: https://doi.org/10.3329/dmcj.v6i2.38212) as the authors had already committed it for publication elsewhere. This error is regretted, and we apologise for any inconvenience.